THE USE OF SIMPLE PRESENT TENSE AND ADJECTIVE IN STUDENTS' DESCRIPTIVE TEXTS - Akhmad Fauzi (INFERENCE: Journal of English Language Teaching, 2020)
This study was conducted to know the use of simple present tense and adjectives by students in Junior High Schools in Indramayu when writing a descriptive text. The method used in this study was Descriptive Qualitative. The procedure employed includes collecting students' work, analyzing the data, interpreting them, and concluding. The result shows that: 1) In the simple present tense, students make many errors when writing a descriptive text to describe people. The most dominant errors made by the students are omission (46%), followed by misformation (33%), then addition (20%), and finally, the misordering (1%). In the use of the adjective, the most errors produced by the students are misformation (39%), followed by omission (38%), misordering (18%), and the least is addition (5%). Students' interlanguage problem usually causes the high frequency of errors made by students. They use their native language's structure in the target language.